The reformatory eaudiobook A novel. - Due, Tananarive (Simon & Schuster Audio, 2023)
* Los Angeles Times Book Prize Winner * New York Times Notable Book * Locus Award Finalist * Winner of the Bram Stoker Award and the Shirley Jackson Award * "You're in for a treat...one of those books you can't put down...Due hit it out of the park." —Stephen King A gripping, page-turning "masterpiece" (Joe Hill, #1 New York Times bestselling author of The Fireman ) set in Jim Crow Florida that follows Robert Stephens Jr. as he's sent to a segregated reform school that is a chamber of terrors where he sees the horrors of racism and injustice, for the living, and the dead. Gracetown, Florida June 1950 Twelve-year-old Robbie Stephens, Jr., is sentenced to six months at the Gracetown School for Boys, a reformatory, for kicking the son of the largest landowner in town in defense of his older sister, Gloria. So begins Robbie's journey further into the terrors of the Jim Crow South and the very real horror of the school they call The Reformatory. Robbie has a talent for seeing ghosts, or haints. But what was once a comfort to him after the loss of his mother has become a window to the truth of what happens at the reformatory. Boys forced to work to remediate their so-called crimes have gone missing, but the haints Robbie sees hint at worse things. Through his friends Redbone and Blue, Robbie is learning not just the rules but how to survive. Meanwhile, Gloria is rallying every family member and connection in Florida to find a way to get Robbie out before it's too late. The Reformatory is a haunting work of historical fiction written as only American Book Award–winning author Tananarive Due could, by piecing together the life of the relative her family never spoke of and bringing his tragedy and those of so many others at the infamous Dozier School for Boys to the light in this riveting novel.